p53-specific CD8+ T-cell responses in individuals with cutaneous squamous cell carcinoma. - Black, A; Bailey, A; Jones, L; Turner, R; Hollowood, K; Ogg, G (2005)
BACKGROUND: Systemic immunosuppression is a significant risk factor for cutaneous squamous cell carcinoma (SCC). p53 is mutated and overexpressed in up to 90% of cutaneous SCC lesions. Despite considerable evidence that the immune response is important in the control of cutaneous SCC, there are no studies documenting potential tumour-associated antigens. OBJECTIVES: We tested the hypothesis that individuals with cutaneous SCC have functional circulating CD8+ T cells specific for p53. METHODS: Interferon-gamma immunosorbent assays were used to screen peripheral blood mononuclear cells for reactivity to six p53-derived HLA-A*0201-restricted epitopes from HLA-A*0201-positive patients and controls. RESULTS: We observed significantly elevated frequencies of p53-specific CD8+ T cells in seven of 26 individuals with cutaneous SCC and in one of 10 controls. The degree of lymphocytic infiltrate significantly correlated with the frequency of CD8+ T cells specific for p53 epitopes, but not with control epitopes. CONCLUSIONS: Overall, these data suggest that p53 may represent a target for CD8+ T cells in a proportion of individuals with cutaneous SCC.